Ukuran dan jenis tangkapan post larva lobster pada perbandingan kedalaman dan material perangkap di teluk awang lombok - Didin Komarudin; Mulyono; Wahbi (JURNAL ILMU DAN TEKNOLOGI PERIKANAN TANGKAP, 2023)
Lobster farming still depends on larvae from nature, while the number of larvae caught is small and the size is not uniform. The effectiveness of a trap is caused by various factor. So that in this study it was tested based on the depth test of trap placement and forming material. This study aims to compare the effective trapping materials and identify the trapping depth according to the type and size of post larvae lobsters. The results showed that at the depth of trapping, namely sand lobsters at a depth of 14 meters with a total of 35 heads and a size of 5 cm, was found mostly at a depth of 14 meters with a total of 25 individuals. In the comparison of cement bag trap materials, the catch was the highest, where the cement bag type of lobster larvae that was caught the most was the sand lobster with a total of 154 and in the cement bag, size 5 was obtained with the most number caught. At a depth of 14 meters and cement sack material, the highest number of post-larval lobsters was caught, namely sand lobsters and 5 cm in size, the highest catch was obtained.